2010
DOI: 10.1007/s00216-010-3688-6
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous materials in sensing: morphology and functionality at the meso-interface

Abstract: Mesoporous materials are finding increasing utility in sensing applications. These applications can benefit from a surface area that may exceed 1,000 m(2) g(-1) and fast diffusion of analytes through a porous structure. This article reviews recent developments in mesoporous materials-based sensing and provides examples of the impact of different surface functionality, pore structure, and macro-morphology in an attempt to illustrate the contribution of these factors to the selectivity and sensitivity of a senso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(51 citation statements)
references
References 98 publications
0
50
0
1
Order By: Relevance
“…Organic-inorganic mesoporous silica hybrid materials are attractive for many sensing applications, including heavy metal ions, biomolecules and organic volatiles, because of their stability over a wide range of pH conditions, their inertness in many environments and their transparency in the UV-vis spectrum. 60 Generally, these sensing materials are prepared by the modification of the mesopore surface using alkoxysilanes ((RO) 3 Si-R 0 , R ¼ C 2 H 5 or CH 3 , R 0 ¼ aliphatic with various functional groups (aliphatic or cyclic organic groups including N, S, O, etc.). 60 Studies of sensing and imprinting using PMOs have been reported by several researchers for the removal of organic molecules and metal ions.…”
Section: Pmo Materials As Hosts For Drug and Biomoleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…Organic-inorganic mesoporous silica hybrid materials are attractive for many sensing applications, including heavy metal ions, biomolecules and organic volatiles, because of their stability over a wide range of pH conditions, their inertness in many environments and their transparency in the UV-vis spectrum. 60 Generally, these sensing materials are prepared by the modification of the mesopore surface using alkoxysilanes ((RO) 3 Si-R 0 , R ¼ C 2 H 5 or CH 3 , R 0 ¼ aliphatic with various functional groups (aliphatic or cyclic organic groups including N, S, O, etc.). 60 Studies of sensing and imprinting using PMOs have been reported by several researchers for the removal of organic molecules and metal ions.…”
Section: Pmo Materials As Hosts For Drug and Biomoleculesmentioning
confidence: 99%
“…60 Generally, these sensing materials are prepared by the modification of the mesopore surface using alkoxysilanes ((RO) 3 Si-R 0 , R ¼ C 2 H 5 or CH 3 , R 0 ¼ aliphatic with various functional groups (aliphatic or cyclic organic groups including N, S, O, etc.). 60 Studies of sensing and imprinting using PMOs have been reported by several researchers for the removal of organic molecules and metal ions. [61][62][63][64][65][66][67] Riley and co-workers 61 prepared a PMO material with imprinted sites for selective benzene adsorption.…”
Section: Pmo Materials As Hosts For Drug and Biomoleculesmentioning
confidence: 99%
“…Recently, OMCs have found an increasing number of applications in many areas including catalysis [34e36], adsorption [31,37,38], separation [39,40], sensing [41,42], energy storage [43], supercapacitors and electrochemistry [44,45]. Possibility of kilogram-scale synthesis of high-quality OMC [46] coupled with the use of cheap, green precursors [46,47] can make these materials affordable for all the above-mentioned applications.…”
Section: Introductionmentioning
confidence: 99%
“…Another recent approach allows generation of silicate mesoporous structures with large surface area (up to 1000 m 2 g À1 ) using a surfactant micellar or lamellar phase to fabricate the recognition units of the chemosensor [101]. This large surface area enables high preconcentration of an analyte to enhance detectability.…”
Section: Discussionmentioning
confidence: 99%